The Effect of Organizational Entrepreneurship and Entrepreneurship Orientation on Organizational Performance with Regard to Strategic Entrepreneurship in Industrial Companies in Zanjan Province - reza pirayesh; Vahid Amiri; malihe Jafari; mohammad Imani barandagh (مدیریت بهره وری, 2020)
Entrepreneurship and organizational orientation towards it is now considered an important method of enjoying a competitive climate to institutionalize innovation in the institutional organization and thereby bring about economic prosperity of the country. The purpose of this applied descriptive survey was to explore the relationship between organizational entrepreneurship, entrepreneurial orientation and organizational performance in industrial companies in Zanjan, Iran and to examine the effect of strategic entrepreneurship. The research population comprised all staff members working in the target industrial companies, from among whom a clustered sample of 304 was randomly selected. The research data were collected via the organizational and strategic entrepreneurship Likert scale questionnaire. The research data were further analyzed through Structural Equations Modelling and PLS software and the results showed that the organizational entrepreneurship and entrepreneurship orientation had a significant effect on strategic entrepreneurship which had a positive and significant impact on organizational performance. Moreover, the findings verified the indirect effects of organizational entrepreneurship and entrepreneurial orientation on organizational performance.